Study on antifungal activity of silver/bentonite nanomaterials on soybean phytopathogenic fungi - Châu, Nguyễn Hoài; Thúy, Nguyễn Thị; Hiền, Đào Trọng; Mai, Hoàng Thị; Quang, Nguyễn Văn; Long, Phạm Hoàng; Ngọc, Nguyễn Thị Bích; Thêu, Trần Thị Phương (Vietnam Journal of Biotechnology, 2018)
In the present study, silver nanoparticles were synthesized by chemical reduction method route into the lamellar space of bentonite (Ag/CTS/Bentonite). Silver nitrate (AgNO3) was taken as a metal precursor, sodium borohydride (NaBH4) as a reducing agent, reduction of Ag+ ions and the subsequent formation of Ag nanoparticles, chitosan as a natural polymeric stabilizer and was sticked silver nanoparticles to the surface of bentonite particles, respectively. Manipulating the size and shape of Ag/CTS/Bentonite nanomaterial was characterized using transmission electron microscopy (TEM), spherical silver nanoparticles, as depicted by TEM, were found to have a wide particle size distribution from 5 nm to 90 nm. Meanwhile, the X-Ray flourescence (XRF) spectrum indicated the presence of silver on bentonite particles. Antifungal activity of the synthesized Ag/CTS/Bentonite nanomaterial was investigated against crop pathogenic fungi (Fusarium oxysporium (F. oxysporium) and Rhizoctonia solani (R. solani)) isolated from infected soybean plant in Bac Ninh province by the Plant Protection Research Institute. The assessment of fungicidal activity of the Ag/CTS/Bentonite nanomaterial showed that this product exhibited strong antifungal activity towards soybean pathogenic fungi. At highest nanosilver concentration of the Ag/CTS/Bentonite nanocomposite (400 ppm) sclerotial germination of F. oxysporum was almost inhibited, after 7 days the inhibition effect on sclerotial germination attained 66.70%. For the case of R. solani, after 2 days at 400 ppm silver nanoparticles concentration the inhibition effect on sclerotial germination attained 92.82%. The obtained results suggested that the synthesized Ag/CTS/Bentonite nanomaterial acts as an effective antifungal agent. Thus, it could be used in developing novel antifungal agents for potential applications in agriculture